Analisis Risiko Kandungan Timbal (Pb) pada Air Sumur Kawasan Pertanian di Kenagarian Simpang Tanjung Nan IV Kabupaten Solok - Arlinda, Sari; Mukhlis, Mukhlis; Suksmerri, Suksmerri; Lindawati, Lindawati; Darwel, Darwel (Poltekkes Kemenkes Padang, 2023)
Farmers in the Nagari Simpang Tanjung Nan IV, Solok Regency, are using synthetic pesticides to achieve good agricultural results. Inappropriate pesticide application practices, such as mixing multiple types of pesticides simultaneously, using incorrect dosages, and spraying more than three times a day, have become commonplace. Residents living next to their farmlands have wells as their primary source of clean drinking water, which are located within the agricultural area. This situation poses a contamination risk to the community. The objective of this research is to analyze the risk of lead (Pb) content in well water within the agricultural area of Kenagarian Simpang Tanjung Nan IV. The research design employs the Environmental Health Risk Analysis (ARKL) method. The research findings indicate that Pb concentrations in the water range from 6,735 mg/L to 53,492 mg/L, exceeding the quality standards set by the Ministry of Health Regulation No. 32 of 2017. A significant portion of the population frequently experiences health issues, with an intensity of 66.7%. The average lifetime Risk Quotient (RQ) is 1.11, indicating a risk of pesticide poisoning in the community. Therefore, it is recommended that the community limits the use of pesticides and uses boiled water for daily consumption in an effort to minimize the danger of exposure to heavy metal Pb entering the body through water.